Resonance and the Photographing of Medieval Architecture - Richmond, Stuart (Paideusis)

(untitled) (Canadian Philosophy of Education Society, 2007)
In this essay I aim to convey in text and photographs what it might mean to experience medieval architecture with some degree of connectivity or what Wittgenstein calls, poetically, “resonance.” I provide examples of personal experiences of medieval architecture, and argue for the importance of historical knowledge, sensuous acquaintance, and a sympathetic imagination in gaining a resonant affiliation. Photography, I want to show, is a way of engaging aesthetically with medieval architecture that can, on occasion, lead to the making of images that serve as authentic reminders of the original experience.